There is no pulp necrosis or calcific metamorphosis of pulp induced by orthodontic treatment: biological basis - Alberto Consolaro; Renata Bianco Consolaro
ABSTRACT To biologically explain why the orthodontic treatment does not induce pulp necrosis and calcific metamorphosis of the pulp, this paper presents explanations based on pulp physiology, microscopy and pathology, and especially the cell and tissue phenomena that characterize the induced tooth movement. The final reflections are as follows: 1) the orthodontic movement does not induce pulp necrosis or calcific metamorphosis of the pulp; 2) there is no literature or experimental and clinical models to demonstrate or minimally evidence pulp alterations induced by orthodontic movement; 3) when pulp necrosis or calcific metamorphosis of the pulp is diagnosed during orthodontic treatment or soon after removal of orthodontic appliances, its etiology should be assigned to concussion dental trauma, rather than to orthodontic treatment; 4) the two pulp disorders that cause tooth discoloration in apparently healthy teeth are the aseptic pulp necrosis and calcific metamorphosis of the pulp, both only induced by dental trauma; 5) the concussion dental trauma still requires many clinical and laboratory studies with pertinent experimental models, to increasingly explain its effects on the periodontal and pulp tissues.